Extension Cord: Powering adult education through Cooperative Extension programs - Jackson C Alexander; Kenda S Grover; Kit Kacirek; Shelly Walters (Adult Education Research Conference, 2017)
Cooperative Extension provides opportunities for adult learning in a variety of settings. The study identified perceptions of county agents related to their role in community development and adult education.
Keywords: cooperative extension; adult education; rural development